Attic retraction pocket: a review - Swain, Santosh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Attic retraction pocket (ARP) is one of the important sequelae of eustachian tube dysfunction or otitis media with effusion. It is associated with the loss of original histological and anatomical structure at the attic region. Clinical observation usually shows that negative nasopharyngeal pressure is associated with the development of ARP. However, LaPlace’s law states that the pressure within a sphere varies with the inverse of the radius, which gives a dynamic explanation for why the pars flaccida retract more frequently than the pars tensa leading to the development of ARP. It may develop ossicular chain erosion, cholesteatoma formation, and potentially life-threatening complications due to cholesteatoma. It is thought that blockade of the tympanic isthmus results in isolation of the attic and adjacent middle ear spaces and that subsequent makes negative pressure in these spaces leading to pars flaccida retraction. The severity of ARP with cholesteatoma varies from well-localized pathology to advanced involvement with complications. The choice of treatment is surgery that depends on the initial pathology, which is also associated with hearing outcomes and the rate of recurrence. This review article discusses on epidemiology, etiopathology, classification, clinical manifestations, diagnosis, treatment, and prognosis of ARP.